2015
DOI: 10.1111/1541-4329.12078
|View full text |Cite
|
Sign up to set email alerts
|

Toward Determining Best Practices for Recruiting Future Leaders in Food Science and Technology

Abstract: There is a shortage of qualified food scientists in the workforce that has adverse consequences for the quality and safety of our food supply. The Institute of Food Technologists and other institutions have initiated and continue to initiate outreach programs; however, an analysis of the effectiveness of these efforts has not yet come to fruition. The potential for determining best practices in recruitment is infinite. This manuscript provides a brief review of the possibilities for leveraging Social Cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…A limitation of this study was the sample size of 44 participants was relatively small compared to the population of approximately 4,000 undergraduates enrolled in food science and technology (Stevenson, ), and therefore, the interpretation of these findings should be treated as a pilot study. However, our sample represented students from eight different universities and was diverse in terms of gender and race.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of this study was the sample size of 44 participants was relatively small compared to the population of approximately 4,000 undergraduates enrolled in food science and technology (Stevenson, ), and therefore, the interpretation of these findings should be treated as a pilot study. However, our sample represented students from eight different universities and was diverse in terms of gender and race.…”
Section: Discussionmentioning
confidence: 99%
“…Introducing students to food science before they have entered college is critical to growing enrollment in food science programs and filling the need in the job market. Although current methods led by The Institute of Food Technologists have seen a recent boost in the enrollment of food science programs (Stevenson, ), research is needed to elucidate other methods for the introduction of food science to high school curricula. Therefore, research was conducted to determine if students in biology, with no background in chemistry, could comprehend food science principles.…”
Section: Introductionmentioning
confidence: 99%
“…Recent trends have displayed an alarming gap between the workforce demand for qualified Food Science and Technology graduates and the supply of appropriately qualified graduates capable of filling these employment gaps (Johnston et al., ; STEM Food and Ag Council, ; Stevenson, ). The inability for institutions of higher education to supply the overall agricultural, food, and natural resources industries with a sufficient number of qualified graduates has led to numerous calls for reform in undergraduate education programs (Johnston et al., ; National Research Council, ; STEM Food and Ag Council, ).…”
Section: Introductionmentioning
confidence: 99%
“…As part of their recommendations for the reform of undergraduate education, the National Research Council () suggested, “academic institutions offering undergraduate education in agriculture should engage in strategic planning to determine how they can best recruit, retain, and prepare the agriculture graduate of today and tomorrow” (p. 5). Although recruiting students to enter the profession requires significant effort and strategic action (Stevenson, ), retaining students once they are enrolled in a Food Science and Technology program is a separate, yet equally complex, task. The benefits of student retention on the student, the university, and the industry have been well documented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation